Corporate governance models in business performance: empirical evidence in portuguese companies listed on Euronext Lisbon - Pires, Amélia M.M. (2016)
The last few years were marked by differences of interests in the relationships established in the organizational structure and with consequences in terms of its added value created. With this become necessary to introduce mechanisms to align interests and supervise the activities of agents, in general, and shareholders and managers, in particular. This issue intersects with the topic of models of Corporate Governance (CG) and gains relevance following the latest international financial scandals. In this regard, and based in a sample of 48 enterprises listed on the Lisbon Stock Exchange it was sought to verify the existence of a positive association between the characteristics of the most widely used CG model in Portugal and business performance having been established 8 research hypotheses. The results obtained allowed to validate five of these research hypotheses leading to the conclusion that there is a positive association and statistically significant among the variables model of CG, size of the Board of Directors (CA), the number of independent members on the Board of Directors, existence of different people in the Board of Directors and Chief Executive Officer (CEO) role of president, independence of the CEO and business performance.